Analisa Pengendalian Kebisingan Pada Penggerindaan Di Area Fabrikasi Perusahaan Pertambangan - Indri Setyaningrum; Baju Widjasena; - Suroto (Jurnal Kesehatan Masyarakat (Undip), 2014)
The intensity of the noise in the work area that exceeds the limit can interfere the hearing health of the workers. Noise can be controlled using hierarchy of hazard control which are technique of elimination, substitution, isolation, engineering, administrative and personal protective equipment (PPE). The purpose of the study is to analyze the grinding noise control in the fabrication area. This research is a qualitative research method with observation and depth interviews. The subjects of this study were workers at the grinding, fabrication group leader, and expert of K3 company. From the research we know that the company control the noise using hierarchy of hazard control are isolation, engineering, administrative and personal protective equipment (PPE) because of the economical factor the company decides to using PPE method to their employees. The lack of supervision and strict rules to many workers in the field who do not wear PPE when working, causing the audiometric hearing disturb is still high. The company should prioritised the removal of the loss hearing cause. The company suggested to combine the method of engineering / mechanical engineering with method of personal protective equipment and administrative method to control noise